2018
DOI: 10.1007/s00223-018-0427-z
|View full text |Cite
|
Sign up to set email alerts
|

Normal Bone Microstructure and Density But Worse Physical Function in Older Women Treated with Selective Serotonin Reuptake Inhibitors, a Cross-Sectional Population-Based Study

Abstract: Depression in the elderly is today often treated with selective serotonin reuptake inhibitors (SSRIs) because of their favorable adverse effect profile. However, treatment with SSRIs is associated with increased risk of fractures. Whether this increased risk depends on reduced bone strength or increased fall risk due to reduced physical function is not certain. The aim was therefore to investigate if treatment with SSRIs is associated with impaired bone microstructure, bone density, or physical function in old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
0
14
1
Order By: Relevance
“…An initial manual screening was performed based on home address, to ensure that the participants were within the right age range and to exclude those residing in special housing. The inclusion and exclusion criteria have been described earlier [ 21 , 22 ]. The study included 3028 elderly women.…”
Section: Methodsmentioning
confidence: 99%
“…An initial manual screening was performed based on home address, to ensure that the participants were within the right age range and to exclude those residing in special housing. The inclusion and exclusion criteria have been described earlier [ 21 , 22 ]. The study included 3028 elderly women.…”
Section: Methodsmentioning
confidence: 99%
“…Skeletal microstructure has only recently begun to be evaluated in those taking anti-depressants. A recent study using high resolution peripheral quantitative computed tomography (HR-pQCT) indicated no association between SSRI use and skeletal microstructure in older women [16]. In contrast, another study assessing bone microstructure using the trabecular bone score (TBS) found SSRI use to be associated with lower TBS but the association was not independent of covariates [23].…”
Section: Introductionmentioning
confidence: 98%
“…Data regarding the effects of anti-depressants, particularly SSRIs and SNRIs, on the musculoskeletal system in humans are limited. There are conflicting data with regard to the effect of SSRIs on BMD as measured by DXA and few data in SNRI users [15][16][17][18][19][20][21][22]. Skeletal microstructure has only recently begun to be evaluated in those taking anti-depressants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26] To support this, selective serotonin reuptake inhibitors were also related to impaired physical activity without decreased bone mineral density or bone microstructure in a population-based study. [27]…”
Section: Discussionmentioning
confidence: 99%